2014
DOI: 10.1167/iovs.13-12957
|View full text |Cite
|
Sign up to set email alerts
|

siRNA Silencing of the Mutant Keratin 12 Allele in Corneal Limbal Epithelial Cells Grown From Patients With Meesmann's Epithelial Corneal Dystrophy

Abstract: Combined with an effective delivery vehicle this siRNA approach represents a viable treatment option for prevention of the MECD pathology observed in K12-Leu132Pro heterozygous individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Cas9/sgRNA constructs were delivered to the mouse cornea by intrastromal injection, as previously described (Courtney et al . 8 ). Both a guide targeted to Luc2 (sgLuc2 - right eye) and a non-specific control guide (sgNSC - left eye) were injected intrastromally in a total volume of 4 µl of PBS at a concentration of 500ng/µl.…”
Section: Methodsmentioning
confidence: 99%
“…Cas9/sgRNA constructs were delivered to the mouse cornea by intrastromal injection, as previously described (Courtney et al . 8 ). Both a guide targeted to Luc2 (sgLuc2 - right eye) and a non-specific control guide (sgNSC - left eye) were injected intrastromally in a total volume of 4 µl of PBS at a concentration of 500ng/µl.…”
Section: Methodsmentioning
confidence: 99%
“…Additional K12 expression constructs previously described 7 were used to assess allele specificity and potency. Firefly luciferase plasmids with the full mRNA sequence for either K12-WT or K12-L132P inserted 3′ of the stop codon, hereafter named as K12WT-Luc and K12LP-Luc, respectively, 7 and expression plasmids for mature haemagglutinin (HA)-tagged K12-WT and K12-L132P protein, 10 with plasmids hereafter known as K12WT-HA and K12LP-HA, respectively, were used. An expression construct for Renilla luciferase (pRL-CMV, Promega, Southampton, UK) was used for the dual-luciferase assay to normalize transfection efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Using the same cDNA samples assessed by quantitative reverse transcriptase-PCR, pyrosequencing was carried out to determine the ratio of remaining K12-L132P mRNA to K12-WT mRNA, exactly as described previously. 10 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic benefit was now demonstrated in cells from patients and animal models, and promising results of the first phase Ib clinical trial using siRNA-based allele-specific therapy were reported in pachyonychia congenita, an inherited skin disorder due to dominant mutations in the keratin 6 gene [31]. The allele-specific siRNA silencing of the mutant keratin 12 allele was also applied in corneal limbal epithelial cells grown from patients with Meesmann's epithelial corneal dystrophy [32,33]. It has also been shown that modified siRNAs conferring allele-specific silencing against disease-causing ALK2 mutants found in fibrodysplasia ossificans progressiva, without affecting normal ALK2 allele [34].…”
Section: Allele-specific Rnaimentioning
confidence: 99%